2021
DOI: 10.5194/agile-giss-2-7-2021
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Typing and Speech For Map Metadata Creation

Abstract: Abstract. Metadata is key to effective knowledge organization, and designing user interfaces that maximize user performance and user experience during metadata creation would benefit several areas of GIScience. Yet, empirically-derived guidelines for user interfaces supporting GI-metadata creation are still scarce. As a step towards mitigating that gap, this work has implemented and evaluated a prototype that produces semantically-rich metadata for web maps via one of two input modalities: typing or speech. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As far as UMIs are concerned, their uniqueness as geospatial resources can be highlighted from two perspectives that are inherited from maps: being a tool and a representation of geographic space (Lai & Degbelo, 2021). As a tool, UMIs are helpful to create and communicate (visual) stories about geographic phenomena; while being a knowledge representation, they index information by location in a plane as opposed to using sentences as primary units to organize knowledge (Lai & Degbelo, 2021). To describe the semantics of UMIs, we need to understand the composing elements and element-wise relationship of the map images.…”
Section: Design Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as UMIs are concerned, their uniqueness as geospatial resources can be highlighted from two perspectives that are inherited from maps: being a tool and a representation of geographic space (Lai & Degbelo, 2021). As a tool, UMIs are helpful to create and communicate (visual) stories about geographic phenomena; while being a knowledge representation, they index information by location in a plane as opposed to using sentences as primary units to organize knowledge (Lai & Degbelo, 2021). To describe the semantics of UMIs, we need to understand the composing elements and element-wise relationship of the map images.…”
Section: Design Concernsmentioning
confidence: 99%
“…The cognitive tool layer focuses on the fact that UMIs are tools for constructing and communicating visual representations about geographic entities and phenomena, they present "refined insights" (Lai & Degbelo, 2021), and thus mainly describes its various features and elements related to visual cognition. Different types of ubiquitous maps differ in their constituent elements, expression contents, and expression methods.…”
Section: Model Overviewmentioning
confidence: 99%
“…The potential of speech recognition and NLP in geospatial applications has been the focus of numerous studies. For instance, Pei-Chun Lai and Auriol Degbelo [4] designed a prototype web map application utilising both text and speech inputs to retrieve metadata. Thomas Gilbert [5] developed VocalGeo, a tool using speech recognition for the interactive teaching of geospatial information.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Goel et al (2011) proposed an approach to retrieve pictures from web-based image search engines and PDF documents, and categorised them as maps and non-maps. Work on semantic annotation proposed computational ontologies to annotate different aspects of geovisualizations for improved search, for example: map content (Mai et al, 2022;Scheider et al, 2014b), metadata about maps (Scheider et al, 2014b), map legend (Gao et al, 2016), what users learned during their interaction with maps (Degbelo, 2021), and the process of creating maps (Mai et al, 2022;Huang and Harrie, 2020). Lai and Degbelo (2021) compared the use of typing and speech as modalities for the semantic annotation of maps and reported that combining both could be beneficial to GI-metadata creation user interfaces.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Work on semantic annotation proposed computational ontologies to annotate different aspects of geovisualizations for improved search, for example: map content (Mai et al, 2022;Scheider et al, 2014b), metadata about maps (Scheider et al, 2014b), map legend (Gao et al, 2016), what users learned during their interaction with maps (Degbelo, 2021), and the process of creating maps (Mai et al, 2022;Huang and Harrie, 2020). Lai and Degbelo (2021) compared the use of typing and speech as modalities for the semantic annotation of maps and reported that combining both could be beneficial to GI-metadata creation user interfaces. Prototypical tools to enable the search of static historical maps were presented in (Scheider et al, 2017(Scheider et al, , 2014a, and examples of websites to browse static historical maps include the Alexandria Digital Library (Goodchild, 2004; UC Santa Barbara Library, 2022) and the David Rumsey Map Collection (Cartography Associates, 2022).…”
Section: Introduction and Related Workmentioning
confidence: 99%